The results of correction of endothelial dysfunction in type 2 diabetes mellitus in patients with diabetic retinopathy and associated hypertension - L. K. Moshetova; I. V. Vorobieva; D. N. Gigineishvili; E. A. Neshkova; V. A. Metelskaya; N. G. Gumanova; V. I. Alekhnovich,; G. V. Podguzov (Oftalʹmologiâ, 2014)
Purpose:Studying the dynamics of clinical functional and morphological status of the retina against the metabolic and antiischemic therapy of retinopathy in type 2 diabetes associated with hypertension based on indicators in the tear fluid and serum nitric oxide metabolites.Methods: Following a standard ophthalmologic examination of 50 patients, among which are the two groups are similar in age andsex. The main group (n = 37) with Cd 2, DR and DR I and II hypertension II, III stage, the average age was 62,2±1,2 years, antihypertensive therapy — an ACE inhibitor Prestarium (5 mg). Patients of the group were divided into two subgroups: the first subgroup (n = 19)who underwent parabulbarnom Mildronate (10 injections), the second subgroup (n = 18), which the drug was administered intranasally Semaks (20 days). The control group (n = 13) healthy (n = 6), and patients with type 2 diabetes without DR and GB (n = 7). Quantitative determination of the stable NO metabolites was determined in biochemical method samples of serum and lacrimal fluid.Results: After completing a course of therapy for patients of the first subgroup marked decrease in retinal thickness (p ≤ 0,05) in f.centralis, temporal lobe, the upper and lower bands parafovea and temporal area perifovea, while in the second group — in 9 areas of the macular area (p ≤ 0.05). It is also noted a significant increase in sensitivity to light in the macular area in patients of both subgroups (MAIA). On the background of the treatment observed reduction of NOx in the lacrimal fluid and serum of patients in both clinical groups. Thus, reduction of NOx in the lacrimal fluid was statistically significant in the subgroup of patients receiving anti-ischemic therapy semaks (p <0,05). In both clinical subgroups after treatment revealed correlation between systolic blood pressure and the level of NOx in the serum (r = 0,4; p <0,05).Conclusion: The positive effect (p <0,05) antioxidant (Mildronat) and ischemic (Semaks) therapy on clinical and functional and morphological parameters of the retina in patients with retinopathy in type 2 diabetes in combination with GB. NOx reduction in the tear fluid and serum was associated with decreased severity of clinical symptoms DR I and II, the resulting vascular endothelial dysfunction. This allows us to consider this as an effective therapeutic intervention aimed at preventing the onset and progression of retinopathy in the combined course of type 2 diabetes and hypertension.